Engagement with candidate posts on Twitter, Instagram, and Facebook during the 2019 election - Boulianne, Shelley; Larsson, Anders Olof (My University, 2021)
Social media are critical tools offering connections between political actors, voters, and journalists. However, existing scholarship rarely assesses how user engagement differs by platform, content, and function of the post. We examine Facebook (n = 938), Instagram (n = 258), and Twitter (n = 1771) posts by the leaders of three major political parties in Canada during the 2019 Federal Election. Across all three platforms, Liberal Leader Trudeau’s posts receive the most engagement. On Twitter, attack posts receive slightly more engagement and interaction posts receive less engagement, compared with other platforms. While policy posts produce lower levels of engagement across platforms, Facebook is distinctive in yielding the lowest levels of user engagement on policy posts. In sum, our findings suggest that political leaders should tailor the content of their social media posts to different platforms.
Keywords: audience engagement; Canada; election; Facebook; Instagram; social media; Twitter